Role of emotional labour in managing job stress for frontline officers in a service industry: the case of National Social Security Authority - Doro, Lissa (Midlands State University, 2019)
Frontline officers play an important role in organisations, as they are directly involved with customers and clients who are the lifeline of any organization. It is because of this function as the go- between the company and the customers that front line officers effectively need to manage stress so as to effectively deliver quality service. Coupled with various stressors such as role overload, role ambiguity, socio-economic stressors, work/life imbalance, and rigid organizational policies as well as disgruntled customers, frontline officers are bound to experience job stress on a greater magnitude than other employees. The researcher observed that NSSA does not have a stress management policy in place, hence this particular study. The main objective of this dissertation was to examine the role of emotional labour in managing job stress for frontline officers in a service industry. This study used a qualitative research approach. A sample size of 35 participants was drawn from 70 frontline employees at the NSSA Head office and Harare Regional Office, however there were a total of 31 respondents. Semi structured interviews and open ended questionnaires were used for this study. The main causes of job stress that were highlighted by respondents are work overload, economic uncertainties, nature of work, work-life imbalance, management/leadership style and difficult customers. It was discovered that deep acting is the emotional labour strategy that is effective in stress management as compared to surface acting.